THERAPEUTIC EXPERIMENTS WITH ANTICROTALUS AND ANTIMOCCASIN SERA - Noguchi, Hideyo (The Rockefeller University Press, 1906)
1. The action of different antivenins is highly, although not absolutely, specific for the venoms for which they are prepared. The antivenomous effect is demonstrable by experiments on toxicity (in vivo) and on hæmolysis (in vitro). 2. Anticrotalus and antimoccasin sera possess therapeutic properties of high degree. By their employment before the stage of extreme prostration has been reached, poisoned guinea-pigs can be saved. 3. The standardization of antivenins must be made separately for the antitoxic and antihæmolytic actions, since these do not bear a constant and invariable relation to each other.